23 Concerv: a prospective trial of conservative surgery for low-risk early stage cervical cancer. (18th September 2019) - Schmeler, K; Pareja, R; Lopez, A; Fregnani, JH; Lopes, A; Perrotta, M; Tsunoda, A; Cantu, D; Carvajal, JM; Ramondetta, L; Manchana, T; Crotzer, D; et al.
Abstract : Objectives: To prospectively evaluate the oncologic outcomes of conservative surgery in women with early stage cervical cancer. Methods: From 2009–2019, a prospective, multicenter study evaluated conservative surgery in 100 eligible women from 16 sites in 9 countries. Eligibility criteria included: 1) FIGO 2009 stage IA2-IB1 cervical carcinoma; 2) squamous or adenocarcinoma histology; 3) tumor size <2 cm; 4) no lymphovascular space invasion; 4) depth of invasion <10 mm; and 5) cone biopsy with negative margins (one repeat cone biopsy allowed). Women desiring future fertility underwent cervical conization and pelvic lymph node (LN) assessment consisting of sentinel LN biopsy and/or full pelvic LN dissection. Those not desiring future fertility underwent simple hysterectomy with LN assessment. All pathologic specimens were centrally reviewed by an expert gynecologic pathologist. Results: Median age at surgery was 38 years (range; 23–67). Stage at diagnosis was IA2 (33%) and IB1 (67%). Histologic type included squamous cell carcinoma (48%) and adenocarcinoma (52%). Surgery included conization and LN assessment in 44/100 (44%) women and simple hysterectomy with LN assessment in 56/100 (56%) women. Minimally invasive surgery (MIS) was performed in 96/100 (96%) patients: laparoscopic in 83; robotic in 13. Positive LNs were noted in 5/100 women (5%). Residual disease in the hysterectomy specimen was diagnosed in 1/56 patients (1.8%). Median follow-up was 25 months (range 0–71). To date, recurrent disease has been diagnosed in 3 patients (3%). Conclusions: Conservative surgery is oncologically safe in women with early stage, low-risk cervical carcinoma.